Programmable Bidirectional Mechanical Metamaterial with Tunable Stiffness and Frictional Energy Dissipation. Issue 7 (14th April 2022) - McCrary, Aaron; Hashemi, Mohammad Saber; Sheidaei, Azadeh
Abstract: Energy‐dissipating mechanical metamaterials possess broad applications where absorbing shocks and isolating vibrations within monolithic and sandwich composite structures are required. This study presents the design of a novel bidirectional mechanical metamaterial with tunable stiffness and energy dissipation. By leveraging the phenomenon of Coulomb friction, the metamaterial dissipates energy when a small gap closes and two walls slide across one another under planar loading. The conceptual design of the metamaterial is parameterized, so the material behavior can be tailored to a particular application. A computational framework is built, using finite element analysis and a multi‐objective genetic algorithm to maximize the volumetric energy dissipation such that the unit cell does not undergo plastic deformation. The finite element mesh used in this analysis is first parametrically optimized to minimize simulation time while remaining within a global error threshold. The optimal unit cell is arrayed into a bulk material, formed into a hollow cylinder, and simulated under a compression cycle for different metamaterial densities. A prototype of the hollow cylinder is 3D printed via fused deposition modeling and is tested. Both the simulated and experimental results demonstrate the repeatability of the energy‐dissipating property with a strong correlation. Abstract : This study presents the design of a novel bidirectional mechanical metamaterial with tunable stiffness and energy dissipation. This study uses finite element analysis and a multi‐objective genetic algorithm to maximize energy dissipation and mitigate plastic deformation. The optimal unit cell then arrays into a bulk material, which is simulated, 3D printed, and cycle tested. Correlation between simulations and experiments demonstrates the energy‐dissipating property's repeatability.